ChemInform Abstract: Catalytic Regioselective Synthesis of Pyrazole Based Pyrido[2, 3‐d]pyrimidine‐diones and Their Biological Evaluation. Issue 27 (8th July 2014) - Satasia, Shailesh P.; Kalaria, Piyush N.; Raval, Dipak K.
Abstract The synthesized pyrazole based pyrido pyrimidine‐diones are evaluated for their in vitro antimicrobial, antituberculosis and antimalarial activities.